2022
DOI: 10.20944/preprints202207.0130.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial Impairment: A Common Motif in Neuropsychiatric Presentation? The Link to the Tryptophan-Kynurenine Metabolic System

Abstract: Nearly half a century has passed since the discovery of cytoplasmic inheritance of human chloramphenicol resistance. The inheritance was then revealed to take place maternally by mitochondrial DNA (mtDNA). Later, a number of mutations in mtDNA were identified as a cause of severe inheritable metabolic diseases with neurological manifestation, and the impairment of mitochondrial functions has been probed in the pathogenesis of a wide range of illnesses including neurodegenerative diseases. Recently growing numb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(8 citation statements)
references
References 312 publications
0
8
0
Order By: Relevance
“…KYN is neuroprotective and evidence suggest its lower levels in neurodegenerative diseases and ASD. Growing evidence has revealed that mitochondria have a close link to KYN metabolism and that mitochondrial dysfunction and the activation of the KYN system contribute to the pathogenesis of neurodevelopmental disorders [134]. Thus, potential strategies of clinical neuroprotection using novel kynurenine metabolites and analogues could be a new approach toward treatment of ASD [135].…”
Section: Discussionmentioning
confidence: 99%
“…KYN is neuroprotective and evidence suggest its lower levels in neurodegenerative diseases and ASD. Growing evidence has revealed that mitochondria have a close link to KYN metabolism and that mitochondrial dysfunction and the activation of the KYN system contribute to the pathogenesis of neurodevelopmental disorders [134]. Thus, potential strategies of clinical neuroprotection using novel kynurenine metabolites and analogues could be a new approach toward treatment of ASD [135].…”
Section: Discussionmentioning
confidence: 99%
“…Autism is a spectrum characterized by a wide range of persistent shortages in social interaction, impaired communication skills, restricted-repetitive forms of behavior, and the loss of social interests or activities. These social communication and interaction impairments may be due to impaired social signaling interpretation and failure to guide proper behaviors[ 6 ]. The exact mechanisms for these behavioral abnormalities are not yet defined.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also showed that SSRIs are usually used as the first-line treatment for MDD. However, only 42-53% of patients treated with SSRIs have improved their condition, and medication for treatmentresistant depression remains a challenge (Tanaka et al, 2022). Biased cognition and maladaptive behavior patterns are considered to be the key factors leading to the development and persistence of depression.…”
Section: Introductionmentioning
confidence: 99%